Gender roles in young adult novels and implications for teaching practice - GABOR, MIRASOL JADE (Archīum Ateneo, 2018)
The study applied a combination of qualitative and critical content analysis in doing a close reading of three young adult novels used in the classroom instruction for a middle school English curriculum in the Philippines. It was done inorder to reveal existing portrayal of gender roles in young adult novels assigned to students of an exclusive school for boys and the gender representations that accompany them. Through the analysis, the study also aimed to reveal values highlighted in the novels and what were possible implications of the results for educators in the middle school classroom instruction. Three young adult novels were selected in order to collect a total of four protagonists to be analyzed composed of two male and two female protagonists. Descriptive statements pertaining to each of the characters were categorized according to Sandra Bem's Sex-Role Inventory (1974), and then analyzed using Sandra Bem's Gender Schema Theory (1983). Three out of four of the protagonists showed to be breaking gender stereotypes. Putting emphasis on the results can pave the way to richer classroom discussions about gender representations and values highlighted through their characterizations. The data can also be used to promote gender sensitivity in both students and teachers which can then lead to more inclusive classroom discussions, implemented activities and inclusive learning environment.